A design environment for downstream processes for Bioprocess-Engineering students - van der Schaaf, H.; Vermue, M.; Tramper, J.; Hartog, R. (European journal of engineering education, 2003)
A bioprocess engineer should have at least a set of basic design skills. Bioprocess design is a complex cognitive skill, which should be trained in every year of an academic Bioprocess-Engineering curriculum. However, there is little existing learning material to support the initial training of design skills early in the curriculum. For this reason a web-based DownStream Process Design environment has been developed, called DSPD. This article describes the design criteria for the development of this design environment. It describes the design environment itself and it gives an impression of the use of the design environment in a course for first-year students.